Chinese perceptions of corporate social responsibility: an analysis of annual reports in the housing sector (Chinese perceptions of corporate social responsibility). Issue 13 (3rd October 2022) - Xiong, Bo; Ye, Kunhui; Skitmore, Martin; Jiang, Weiyan; Qin, Beibei
Abstract: Corporate social responsibility (CSR) has been widely accepted as essential for sustainable development and, with the occurrence of such disasters as food quality scandals and building collapses, its importance has been increasingly recognised in China over the past decade. At the same time, despite property development being frequently linked in the mass media with unaffordable housing prices, bribery, and poor construction quality, many large developers have instituted programmes to improve their CSR presence. However, the perceptions of property development organisations of what CSR means to them are as yet unclear. The aim of this paper, therefore, is to better understand the way CSR is seemingly perceived by property developers in China. This is undertaken by analysing CSR disclosure and prioritising information from CSR corporate reports by developers in the housing sector. Three attributes of CSR disclosure information type, responsibility type, and stakeholder type are used to construct an analytical framework for testing of 44 published company reports by content analysis. The findings indicate a greater emphasis on management approaches and ethical responsibilities than commercial goals, with industry and ownership differences pointing to the need to be recognised by the public and future decision-makers.